Association between intraoperative dexmedetomidine and survival outcomes after colorectal cancer surgery: a retrospective cohort study - Chen, Shirong; Gan, Lu; Zhang, Ruosi; Huang, Xiang; Li, Pei; Ni, Jiawei; Liu, Kexuan; Liu, Huamin; Li, Cai (Frontiers in Oncology, 2025)
BackgroundThe impact of dexmedetomidine (DEX) on postoperative survival outcomes in cancer remains controversial. Our study aimed to investigate the influence of intraoperative DEX administration on postoperative mortality outcomes in colorectal cancer patients.MethodsThis was a retrospective cohort study of adult patients undergoing colorectal cancer surgery in a large academic hospital in southern China between 2011 and 2018. Patients were divided into two groups: the DEX group, in which patients received intravenous DEX during the operation, and the non-DEX group. The primary endpoint was overall death or tumor recurrence, deriving two outcome variables: “all-cause death” and “recurrence or death.” Secondary endpoints included total hospital stay, postoperative hospital stay, and postoperative complications. Multivariable Cox regression and propensity score matching were used to control confounders.ResultsA total of 1,367 adult patients were included, of which 485 pairs were matched. Patients who received intraoperative DEX had a lower all-cause death rate (8.0% vs. 14.2%, P = 0.002) and a lower recurrence or death rate (14.8% vs. 23.1%, P = 0.001). Intraoperative DEX administration was associated with a lower risk of all-cause death postoperatively [adjusted hazard ratio (HR) and 95% confidence interval (CI): 0.74, 0.52–1.07 in overall patients; 0.66, 0.45–0.98 in matched patients] compared with non-DEX. The risk of recurrence or death was lower with a marginal significance (HR and 95% CI: 0.75, 0.56–1.01) in matched patients. The total hospital stay and postoperative hospital stay were lower in patients who used DEX than those who did not use it (β and 95% CI: −0.96 [−1.71, −0.22] and −0.95 [−1.47, −0.43], respectively, in matched patients). Meanwhile, the risk of postoperative complications was not associated with DEX.ConclusionsIn patients undergoing colorectal cancer surgery, intraoperative DEX administration was associated with better postoperative survival.